Training of teachers promoting Environmental Education at the University of Cienfuegos - Amil Sellés, Yissel Pérez de Villa; Calzadilla Milian, Oneida (Revista Minerva, 2020)
Environmental education for sustainable development should be the main goal of any educational teaching process, which forces to promote their reorientation, in such a way that it integrates issues inherent to development, its relationship with nature and nature into the teaching curriculum. sustainability, fundamentally from the environmental problems that prevail in today’s world. In this sense, Environmental Education provides a synthesizing vision, necessary for the understanding and interpretation of the nature-society interaction and presupposes the consolidation of a system of knowledge, skills and behavioral values ​​in society in a general sense. For this education to be efficient, it must achieve processes of change that guide humanity towards a system of more harmonious relationships between society and nature and that allow the transition to sustainable levels of development with a decent and equitable quality of life for all societies.